Efektivitas Pemberian Bubur Instan Berbasis Labu Kuning terhadap Peningkatan Berat Badan dan Tinggi Badan Baduta dengan Risiko Stunting di Wilayah Puskesmas Gunung Meriah, Aceh Singkil - Indah Sari Bancin; Ambia Nurdin; Dian Rahayu; Khairuman Khairuman (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Stunting remains a major chronic nutritional problem in Indonesia, including Aceh, and has serious impacts on children’s physical growth and cognitive development. Prevention efforts require appropriate, practical, and sustainable nutritional interventions, including the use of local foods such as pumpkin, which is rich in beta-carotene, vitamin A, carbohydrates, and fiber, and can be combined with animal and plant protein sources. This study aimed to evaluate the effectiveness of an instant pumpkin-based porridge in improving the weight and height of children aged 6–24 months who are at risk of stunting in the Gunung Meriah Health Center area. The study used a quasi-experimental design with a nonequivalent control group involving 41 children divided into intervention and control groups. The intervention group received the instant porridge for 21 days. Data analyzed using paired t-tests and independent t-tests showed significant improvements in the intervention group’s weight and height (p<0.05). The pumpkin-based instant porridge proved effective as a local food–based nutritional intervention and has the potential to be integrated into supplementary feeding programs and regional nutrition policies with broader coverage and longer duration..